OPTIMIZATION OF CHANNEL PERFORMANCE AND CAPACITY ON OPENBTS USING USRP N210 - Prapanca, Muhammad Eksya; Kusmaryanto, Sigit; Kurniawan, Dwi Fadila (Jurnal Mahasiswa TEUB, 2024)
Indonesia, as the largest archipelagic country in the world, with an area of 2 million square kilometers and consists of 17,500 islands, as well as a population of around 250 million people. Facing challenges in the development of telecommunications infrastructure, especially in remote areas, Indonesia faces difficulties in providing equitable telecommunications access, especially in remote areas. Although most villages and sub-districts have been covered by BTS signals, some still experience weak signal constraints or do not get a signal at all. Alternative solutions such as OpenBTS, an open-source software project, are becoming relevant in this context. OpenBTS can help address infrastructure challenges by providing telecommunications services such as phone calls and SMS at lower implementation costs. However, it should be noted that the use of OpenBTS can also face challenges such as delays in service, especially in Non-Line-of-Sight (NLOS) conditions.The purpose of this study is to design an OpenBTS telecommunication network using an Ubuntu 14.04.6-based USRP N210 device. Then improve the quality of use by optimizing the OpenBTS service and testing its reliability in various operational scenarios, including the use of SMS andphone call services.Keywords: GSM, OpenBTS, USRP, SMS, Telephone, Delay